Microwave-assisted synthesis and characterisation of uniform LaPO4nanorods - Nuengruethai Ekthammathat (2018)
Lanthanum phosphate (LaPO4) phosphor materials with one-dimensional (1D) nanorods and nanoparticles were successfully synthesised from LaCl3·7H2O and Na3PO4·12H2O with pH adjusted at the range 1-6 using 37% HNO3by the microwave radiation at 180 W for 60min. X-ray diffraction patterns indicated that the as-synthesised products were hexagonal LaPO4nanostructures. Scanning electron microscopy and transmission electron microscopy analyses showed that these products were nanoparticles, short and long nanorods, controlled by pH of the precursor solutions. Asymmetric stretching and bending vibrations of the PO4groups were detected using Fourier transform-infrared spectroscopy. A possible formation mechanism of LaPO4phosphor materials with 1D nanorods and nanoparticles was also proposed according to the experimental results. © 2012 Taylor & Francis.